2009
DOI: 10.1037/a0015339
|View full text |Cite
|
Sign up to set email alerts
|

Judging the credibility of historic child sexual abuse complainants: How judges describe their decisions.

Abstract: Criminal prosecutions of child sexual abuse alleged to have occurred in the distant past raise myriad challenges. One significant challenge involves assessing the credibility of complainants. In the present study, 51 bench trials involving 87 complainants were coded into categories related to complainants' memory for the offense, as well as credibility of the complainant, reliability of the evidence, and judicial inferences. A total of 4,827 judicial comments were identified and categorized. Judges were more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 60 publications
2
18
0
Order By: Relevance
“…Evaluative reactions are an important component of well-formed narratives (Labov & Waletsky, 1967; Stein & Glenn, 1979), and well-formed narratives are likely to be more convincing (O’Barr, 1982; Pennington & Hastie, 1992). Although we are not aware of any research specifically examining the effects of child witnesses’ production of evaluative reactions on jurors, Connolly and colleagues (2009, 2010) found that judges frequently mentioned alleged victims’ conduct at the time of abuse in justifying their decisions (and conduct included emotional reactions).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Evaluative reactions are an important component of well-formed narratives (Labov & Waletsky, 1967; Stein & Glenn, 1979), and well-formed narratives are likely to be more convincing (O’Barr, 1982; Pennington & Hastie, 1992). Although we are not aware of any research specifically examining the effects of child witnesses’ production of evaluative reactions on jurors, Connolly and colleagues (2009, 2010) found that judges frequently mentioned alleged victims’ conduct at the time of abuse in justifying their decisions (and conduct included emotional reactions).…”
Section: Discussionmentioning
confidence: 98%
“…Children who fail to describe strong negative reactions may be disbelieved, despite the fact that children often state that they were initially confused by the perpetrator’s actions or did not recognize that the actions were wrong (Berliner & Conte, 1990; Sas & Cunningham, 1995). Because children’s reactions to abuse are varied, some have even argued that questions about children’s reactions to alleged abuse should be presumptively inadmissible at trial (Connolly, Price, & Gordon, 2009). These are important questions for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Research has consistently found that delayed or retrospective disclosure of child sexual abuse (CSA) is viewed as being less believable than immediate disclosure (e.g., Connolly, Price, & Gordon, 2009;Cromer & Freyd, 2007). However, it is not uncommon for CSA survivors to delay disclosure, if they ever tell anyone at all.…”
mentioning
confidence: 96%
“…Until the latter part of the 20th century, if a CSA complaint was delayed, a different legal doctrine, the recent complaint doctrine, compelled a judicial warning that the complaint was probably false (Connolly, Price, & Gordon, ). The recent complaint doctrine stated that a victim of sexual assault (the doctrine only applied to sexual assaults) was expected to report the crime at the first available opportunity; failure to do so meant that the trier of fact was required to assume, in the absence of convincing contrary evidence, either that a sexual assault had not occurred or that sex was consensual (Lewis, ).…”
mentioning
confidence: 99%